Association between risky sexual behavior and a psychosocial syndemic among Nigerian men who have sex with men. Issue 2 (3rd April 2019) - Oginni, Olakunle A.; Mapayi, Boladale M.; Afolabi, Olusegun T.; Ebuenyi, Ikenna D.; Akinsulore, Adesanmi; Mosaku, Kolawole S.
Abstract: Background : The HIV epidemic among men who have sex with men (MSM) is reinforced by a psychosocial syndemic, but this has not been investigated in sub-Saharan Africa. This study investigated the psychosocial syndemic and its relationship with risky sexual behavior among Nigeria MSM. Methods : Eighty-one MSM and 81 heterosexual men were compared for risky sexual behavior and psychosocial adversity variables—childhood adversity, intimate partner violence, depressive symptoms, suicidal ideation, substance use, and a derived psychosocial syndemic score. The association between syndemic scores and risky sexual behavior was examined among MSM. Results : MSM had significantly higher rates of individual psychosocial adversities except substance use. There were significant interrelationships between the variables, and syndemic scores were associated with higher-risk sexual behavior. Conclusion : This is the first study to investigate the psychosocial syndemic and its relationship with HIV risk among African MSM. The findings highlight the role of psychosocial adversities in exacerbating the HIV epidemic among MSM in developing countries.